Effect of Dietary Bacillus licheniformis Supplementation on Growth Performance and Microbiota Diversity of Pekin Ducks - Li, Lei; lv, Xueze; Han, Xu; Sun, Chenglei; An, Keying; Gao, Wenwen; Xia, Zhaofei (Frontiers in Veterinary Science, 2022)
This experiment was conducted to investigate the effects of different concentrations of Bacillus licheniformis (B. licheniformis) on growth performance and microbiota diversity of Pekin ducks. Three hundred 1-day-old healthy Pekin ducks were randomly divided into 5 groups with 6 replicates per group and 10 ducks per replicate. The five treatments supplemented with basal diets containing: either 0 (group CON), 200 (group LLB), 400 (group MLB), and 800 (group HLB) mg/kg B. licheniformis or 150 mg/kg aureomycin (group ANT) for 42 days, respectively, and were sacrificed and sampled in the morning of the 42nd day for detection of relevant indexes. The results showed as follows: The feed conversion ratio of the LLB group and MLB groups were lower than the CON group (P < 0.05). The body weight and average daily feed intake of the MLB group were significantly higher than that of the CON group and ANT group (P < 0.05). Compared with the CON group, the MLB group significantly increased the content of IgA (P < 0.05) and proinflammatory IL-6 were significantly decreased (P < 0.05), besides, the activity of SOD and T-AOC were also significantly increased in the MLB group (P < 0.05). The 16S rRNA analysis showed that B. licheniformis treatments had no effect (P > 0.05) on the alpha diversities of the intestine. The addition of B. licheniformis had a dynamic effect on the abundance of cecal microflora of Pekin ducks, and 1-21 d increased the diversity of microflora, while 21d-42 d decreased it. Compared with the CON group, the relative abundance of Epsilonbacteraeota in the MLB group was significantly increased on Day 21 (P < 0.05), and that of Tenericutes in the LLB group was significantly increased as well (P < 0.05). At 42 d, the relative abundance of Bacteroidetes in LLB, MBL, HBL, and ANT groups was significantly increased (P < 0.05). In addition, the addition of B. licheniformis increased the amount of SCAF-producing bacteria in the intestinal microbiota, such as Lachnospiraceae, Collinsella, Christensenellaceae, and Bilophila. The PICRUSt method was used to predict the intestinal microbiota function, and it was found that lipid transport and metabolism of intestinal microbiota in the MLB group were significantly affected. Overall, these results suggest diet supplemented with B. licheniformis improved growth performance, immune status, antioxidant capacity, and modulated intestinal microbiota in Pekin ducks. The optimal dietary supplement dose is 400 mg/kg.